Hints about the multiplicity of WR 133 based on multiepoch radio observations - De Becker, M. (2019)
Several tens of massive binary systems display indirect, or even strong evidence for non-thermal radio emission, hence their particle accelerator status. These objects are referred to as particle-accelerating colliding-wind binaries (PACWBs). WR 133 is one of the shortest period Wolf-Rayet + O systems in this category, and is therefore critical to characterize the boundaries of the parameter space adequate for particle acceleration in massive binaries. Our methodology consists in analyzing JVLA observations of WR 133 at different epochs to search for compelling evidence for a phase-locked variation attributable to synchrotron emission produced in the colliding-wind region. New data obtained during two orbits reveal a steady and thermal emission spectrum, in apparent contradiction with the previous detection of non-thermal emission. The thermal nature of the radio spectrum along the 112.4-d orbit is supported by the strong free-free absorption by the dense stellar winds, and shows that the simple binary scenario cannot explain the non-thermal emission reported previously. Alternatively, a triple system scenario with a wide, outer orbit would fit with the observational facts reported previously and in this paper, albeit no hint for the existence of a third component exists to date. The epoch-dependent nature of the identification of synchrotron radio emission in WR 133 emphasizes the issue of observational biases in the identification of PACWBs, that undoubtedly affect the present census of PACWB among colliding-wind binaries.